RANCANG BANGUN PROTOTIPE SISTEM ATS-AMF BERBASIS MIKROKONTROLER DI PERUMDA AIR MINUM TIRTA SANJIWANI UNIT PRODUKSI BLANGSINGA - Eka Pratama, I Gusti Putu; Indra Partha, Cokorde Gede; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2024)
The continuity of electricity supply from generators to consumers cannot always be guaranteed due to various factors such as planned outages, distribution failures, and the impacts of natural disasters. The Regional Public Water Company (Perumda) Tirta Sanjiwani has adopted generators as Backup Power Sources to ensure the availability of water supply to consumers. However, the Blangsinga Production Unit of Perumda Tirta Sanjiwani faces challenges in switching electricity supply between PLN and the generator set (genset), especially in operations requiring uninterrupted continuity. To overcome the instability of the electricity supply from PLN, the use of automatic systems such as ATS (Automatic Transfer Switch) and AMF (Automatic Main Failure) is necessary. The function of ATS is to switch from PLN to the backup power source (genset) when there is a disturbance or outage in PLN. AMF is responsible for detecting failures in PLN and initiating the genset as well as transferring the load to the backup power source when there is a failure in the main power supply. The ATS-AMF system prototype is designed using voltage sensors, frequency sensors, current sensors, and relays to ensure optimal performance and responsiveness to environmental conditions and power supply conditions.